Food insecurity in paradise - Joshua Gruver; Kimberly Lee; Emily Hayes (Journal of Agriculture, Food Systems, and Community Development, 2024)
Despite being a world-class tourist destination, the U.S. Virgin Islands (USVI—St. Thomas, St. Croix, and St. John) face significant challenges related to diversified crop production, food distribution, and food security. High poverty rates among islanders perpetuated by historical iniquities, frequent hurricane damage, drought, poor soil quality, high food production costs, and limited food distribution networks are just a few of the challenges residents face. Consequently, 97% of the food consumed in the USVI is imported. Frequent hurricane damage, such as the recent damage from Irma and Maria (back-to-back Category 5 storms that hit the islands in 2017) complicated these challenges even more and disrupted food import processes. This manuscript focuses on a case study involving a literature review, participant observation, and a series of semi-structured, face-to-face interviews with key informants about issues related to food insecurity, resilience, and farmer needs regarding business sustainability. The results highlight how the political, economic, and cultural complexities of the USVI stymie efforts to lower barriers related to food accessibility and affordability. The results also reveal a new and vibrant entrepreneurial spirit among native islanders and transplants alike, providing novel entryways into food system change and development. Finally, we share policy implications and next steps toward building agriculture and food system resiliency.